CRPP for Extension Type III Supracondylar Fracture of Humerus by Lateral versus Crossed K Wires – a Comparative Hospital Based Study - K C, Samir; Sharma Kandel, Ishwar; Shrestha, Bhola; Bista, Krishna Bahadur; Dhakal, Rabi Mohan; Parajuli, Pravakar; Shrestha, Debesh; Duwal Shrestha, Sailendra Kumar; Nepal, Prabin; Karki, Netra Bahadur (Journal of Karnali Academy of Health Sciences, 2022)
Background: SCFH accounts for sixty percent of all fractures around elbow. Type III SCFH is unstable. CRPP istreatment of choice. Both the crossed-k wires and lateral-entry k wires have been used successfully; however, superiorityhas not been established. This study compares stability, functional outcomes, radiological outcomes and complications ofthese two methods.Methods: This is a hospital based prospective comparative study undertaken at GMCTH from June 2019 to November2020. Fifty-six children of three to thirteen years with extension type III SCFH were included after taking informedconsent. Ethical clearance was taken from NHRC, Kathmandu. Patients were followed up for three months. Statisticalanalysis was done using SPSS 25 and p value